The Easiest Grammar Understanding for Speaking English Well - Tarmizi Rasul; imam suseno (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
Target of this study is to standardize the English learning and teaching model which is well-granted. The issues faced by the English researchers are to find a method so effectively that semantico grammatical knowledge mastery related to English notion and function which has not found the solution can be formulated as a national standard since the data collected at Jakarta and Depok Junior and senior high schools showed the same issues. The findings of the study showed that there were 90% of Junior and Senior High Schools Students had not been confident to speak English. It is why the researchers introduce the Oral Questioning in L1 and Guidance Method (OQILAG) which is going to be shot and saved in saver and internet localized, and enable the students to use smartphone while speaking English directed by the researcher as a film teacher through LCD (in-focus) in national research next year as a model of e-learning. The data which were stated by English senior teachers showed that there were 90% of Muhammadiyah junior high school unconfident to speak English. Thus, the researchers introduce OQILAG method planned to have been shot and saved in a saver, presented by LCD (in-focus) called e-learning implemented in 2019 research as a national research. Oral questioning in L1 and Guidance (OQILAG) method has succeeded several times to develop of students’ competence and workers as well; however, it has never been examined at private Junior High School, yet developing of the students English skills especially at Muhammadiyah Junior High School was the first times done